Estimated Glomerular Filtration Rate Using Cystatin C is a More Sensitive Marker for Kidney Dysfunction in Nonweight-bearing Individuals. Issue 2 (16th November 2022) - Werneburg, Glenn T.; Hettel, Daniel; Jeong, Stacy; Nemunaitis, Gregory; Taliercio, Jonathan J.; Wood, Hadley M.
Abstract : Purpose: Individuals with neuromuscular disorders and neurogenic lower urinary tract dysfunction are commonly nonweight-bearing with lower lean muscle mass than the general population. We sought to compare estimated glomerular filtration rate equations that include creatinine, cystatin C, or both, in nonweight-bearing individuals and matched ambulatory controls. Materials and Methods: Records were reviewed for individuals with serum creatinine (Cr) and cystatin C (Cys) and diagnosis consistent with nonweight-bearing status, and matched ambulatory controls. The 2021 CKD-EPI (Chronic Kidney Disease-Epidemiology Collaboration) race agnostic equations were used to calculate estimated glomerular filtration rate. Renal function was compared by equation in the overall cohorts and in a patient subset with imaging and/or urinalysis evidence of renal dysfunction. Results: Nonweight-bearing (n = 102) and control populations (n = 204) had similar demographics. In the nonweight-bearing population, estimated glomerular filtration rate differed when calculated using CKD-EPICr, CKD-EPICr+Cys, and CKD-EPICys (107, 93, 80 mL/min/1.73 m 2, respectively, P < .001). The differences in estimated glomerular filtration rate were greater in the nonweight-bearing relative to the control group regardless of CKD-EPI equation pairs compared ( P < .001). In the patient subset with imaging and/or proteinuria evidence of renal dysfunction, the nonweight-bearing population again had different estimated glomerular filtration rate when calculated using CKD-EPICr, CKD-EPICr+Cys, and CKD-EPICys ( P < . 001). Fifty-eight percent of nonweight-bearing individuals with evidence of renal dysfunction on imaging or urinalysis were reclassified into a lower estimated glomerular filtration rate category when using estimated glomerular filtration rateCys relative to estimated glomerular filtration rateCr . Conclusions: Estimated glomerular filtration rate equations containing serum creatinine, cystatin C, or both, validated in mostly ambulatory populations, are not equivalently accurate in estimating kidney function in nonweight-bearing individuals. Comparison of these equations against gold standard glomerular filtration rate measurement is needed to determine which most closely approximates true glomerular filtration rate.